The Quiet Embryo Hypothesis: 20 years on - Leese, Henry J.; Brison, Daniel R.; Sturmey, Roger G. (Frontiers in Physiology, 2022)
This article revisits the hypothesis, proposed in 2002, that the successful development of oocytes and preimplantation mammalian embryos is associated with a metabolism which is “quiet” rather than “active”, within limits which had yet to be defined. A distinction was drawn between Functional Quietness, Loss of quietness in response to stress and Inter-individual differences in embryo metabolism and here we document applications of the hypothesis to other areas of reproductive biology. In order to encompass the requirement for “limits” and replace the simple distinction between “quiet” and “active”, evidence is presented which led to a re-working of the hypothesis by proposing the existence of an optimal range of metabolic activity, termed a “Goldilocks zone”, within which oocytes and embryos with maximum developmental potential will be located. General and specific mechanisms which may underlie the Goldilocks phenomenon are proposed and the added value that may be derived by expressing data on individual embryos as distributions rather than mean values is emphasised especially in the context of the response of early embryos to stress and to the concept of the Developmental Origins of Health and Disease. The article concludes with a cautionary note that being “quietly efficient” may not always ensure optimal embryo survival.